The magic hat - Fox, Mem, 1946-; Tusa, Tricia (Orlando, Fla. : Harcourt, 2006)
A wizard's hat blows into town, but it changes people into different animals when it lands on their heads.
"Voyager books."
Kirkus Starred
Publisher's Weekly
School Library Journal
2.7
K-3.
Keywords: Magic -- Juvenile fiction; Wizards -- Juvenile fiction; Magic -- Fiction; Stories in rhyme; Wizards -- Fiction; Magic -- Fiction; Stories in rhyme; Wizards -- Fiction